Influence of microwave heating in wood preservation on traditional surface coatings - Klinc, Martin (Acta silvae et ligni, 2017)
Microwaves are very effective at wood pest eradication. However, elevated temperatures may pose a risk of damaging surface coatings used on cultural and historical artefacts. Therefore, we monitored changes in patterns of the original paint taken from such objects along with newly prepared coatings. We evaluated visual, mechanical, and chemical modifications of coatings when exposed to microwaves (750W, 2.4GHz), at 60°C or 80°C for 10 min. Whether old or new, only water-based coatings have proven to be resistant to elevated temperatures and no damage was observed at 80°C. Blisters have formed on layers of new oil paints and natural resins due to insufficiently cured film. Temperatures above 80°C may cause melting of coniferous wood resin and thus transport of resin to the surface; on the other hand, temperatures up to 60°C are completely harmless. Mechanical and chemical changes of coatings exposed to microwaves were not observed, but the studies showed that colour and gloss exhibited minor changes.
Keywords: kulturnozgodovinski predmeti; wood; wood coatings; les; wood protection; premazi; zaščita lesa; microwaves; mikrovalovi; heating; segrevanje